Phenolic content and antibacterial properties of various extracts of gambir (Uncaria gambir Roxb) - Rindit Pambayun; Murdijati Gardjito; Slamet Sudarmadji; Kapti Rahayu Kuswanto (Indonesian Journal of Pharmacy, 2007)
Extraction of gambir product with various solvents gave vary in amount of yields, phenolic contents, and its antibacterial properties. Extraction was performed by maseration and Soxhlet methods with some solvents; chloroform, ethyl acetate, ethanol, water, and their combination. The results showed that the highest yield of extract obtained from the solvent combination of ethanol and water (1:1 v/v) both at the maseration and Soxhlet metods, i.e. 84.77 and 87.69 %, respectivelly. Soxhlet method gave the yield of extract higher than that of maseration method. The highest phenolic content was found at the extracts using ethyl acetate both in maseration and soxlet methods, i.e. 88,30 and 90,85 %, respectivelly. Antobacterial properties on the Gram-positive bacteria such as Streptococcus mutans, Staphylococcus aureus, and Bacillus subtilis, indicated that the extracts extracted by using ethyl acetate gave highest inhibitory properties. On the other hand, the extracts did not inhibit Gram-negative bacteria. Extraction was continued by using solvent combination of ethanol and water at the various proportion and at the three levels of temperature, 4, 30, and 60 °C. The results showed that solvent combination of ethanol and water (1:2), gave the highest yield of extracts but lower in phenolic contents and aantibacterial properties.Key words: antibacterial, phenolic content, extract of Uncaria gambir Roxb